The Flipped Classroom with Educational TikTok Improves Students’ Understanding of Local History: Model Kelas Terbalik dengan TikTok Pendidikan Meningkatkan Pemahaman Siswa tentang Sejarah Lokal - Sulastri, Sulastri; Sucipto, Sucipto; Purnamasari, Hetty; Suciati, Suciati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Students' understanding of social studies, especially local history, is an important factor in the success of learning in elementary schools. Specific Background: In the fourth grade of SDN Palengaan Daya 4, it was found that students had a low level of understanding of this subject matter. Knowledge Gap: In addition, the use of modern learning media such as educational TikTok with the Flipped Classroom strategy is still rarely implemented. Aims: This study aims to analyze the impact of the Flipped Classroom strategy combined with educational TikTok content on students' understanding of local history material in the fourth grade of SDN Palengaan Daya 4. Research Method: The study employs a quantitative approach using total sampling techniques on 30 fourth-grade students to ensure the data collected is representative and accurate. Data was collected through comprehension tests and analyzed descriptively and inferentially. Results: The results of the study indicate that the application of the Flipped Classroom strategy with educational TikTok content is effective in improving students' social studies comprehension of local history material. Novelty: This finding can be considered an alternative teaching strategy that aligns with the characteristics of 21st-century learning. Implications: This study provides practical contributions for elementary school teachers in developing engaging and effective learning strategies, supporting the principle of Merdeka Belajar by creating a more independent and creative learning environment, and integrating social media into modern pedagogy. The Flipped Classroom strategy with educational TikTok content not only has practical benefits in improving subject matter understanding but is also theoretically relevant as part of educational transformation in the digital age. Highlights: Combines Flipped Classroom strategy with TikTok-based content. Improves students’ understanding of local history material. Supports innovative, independent, and digital-age learning. Keywords: Flipped Classroom, Educational TikTok, Local History, Social Studies, Elementary Education